Asexual Reproduction and Strobilation of Sanderia malayensis (Scyphozoa, Pelagiidae) in Relation to Temperature: Experimental Evidence and Implications - Massimo Avian; Gregorio Motta; Mattia Prodan; Enrico Tordoni; Vanessa Macaluso; Alfred Beran; Alenka Goruppi; Giovanni Bacaro; Valentina Tirelli (Diversity, 2021)
Sanderia malayensis is a scyphozoan species present in the Indian and Pacific Oceans, ranging from the Suez Canal to Japan. Although this jellyfish is commonly kept in aquariums around the world, there is a knowledge gap regarding its biology and ecology, especially at the polyp stage. In this study, we tested the asexual reproductive activity of S. malayensis at three different temperatures: 10, 15 and 20 °C. Results showed significant increases of polyps at 15 and 20 °C, and a minimum at 10 °C, corresponding with daily budding rates of 6.61% ± 0.92%, 5.85% ± 2.36% and 0.66% ± 0.24%, respectively. Moreover, a second experiment was carried out to report about the ability of S. malayensis to prey on Aurelia solida at the ephyra stage. Unidirectional predation of S. malayensis ephyrae on A. solida and an absence of inverse predation was observed. These results could give new insights on the potential fitness and survival of this species if it will ever invade the Mediterranean Sea.